Analisis Situation Awareness Pengendara Sepeda Motor Berdasarkan Usia, Pengalaman Berkendara, dan Kondisi Waktu Menggunakan Situation Present Assessment Method (SPAM) - Pramudita, Rahmad Hendri; Kusuma, Harun Indra; Sutantio, Erian (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Traffic accidents remain a global challenge, with WHO reporting high mortality rates among individuals aged 5–29 years. In Indonesia, accident trends also show a consistent increase, with an average rise of 6.90% per year from 2019 to 2023, predominantly involving motorcycle riders. This condition highlights the importance of cognitive factors, situation awareness (SA), which plays a role in recognizing, understanding, and predicting events while riding. This study aims to investigate the SA levels of motorcycle riders based on riding experience, age, and time of day using Situation Present Assessment Method (SPAM). This study involves laboratory research and uses primary data in quantitative. The findings indicate that younger and less experienced riders exhibit lower SA levels, and that SA performance at night is lower than in the morning. These results recommend the need for safety training programs that focus on SA development, the preparation of simulation-based educational modules, and the establishment of minimum SA standards for obtaining a driving license.